Environmental Injustice in Palestine: A Political Ecology Perspective - Rahmad, Savina; Shafar, Wildan Ilmanuarif (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2026)
This study examines environmental injustice in Palestine through a political ecology perspective amid the escalation of conflict since 2023. The main issue lies in environmental degradation shaped by power relations that govern access to and control over space and natural resources. This study aims to analyze how power structures within the conflict produce ecological inequalities in Gaza and the West Bank. Using a qualitative approach based on literature review, this research draws on international reports, scholarly articles, and policy documents. The findings show that the destruction of environmental infrastructure, restrictions on mobility, and territorial control function as political mechanisms that limit access to water, land, and livelihoods. From a political ecology perspective, these dynamics reflect the intersection of environmental degradation, social marginalization, and resource control, which reinforce distributive, procedural, and social injustices. This study concludes that environmental degradation in Palestine is embedded within political dynamics that structurally deepen inequality and societal vulnerability among Palestinians.